Framing the Other: cosmopolitanism and the representation of difference in overseas gap year narratives1. (12th March 2013) - Snee, Helene
Abstract: This paper engages with debates surrounding contemporary cosmopolitanism and the outcomes of cultural encounters. It considers if overseas gap years, often put forward in the UK as a way of becoming a global citizen, enable young Britons to 'broaden their mind'. I explore representations of the people and places encountered during these periods of time out through an analysis of young people's travel blogs. Four key themes are highlighted in these narratives: the exotic place; feeling 'out of place'; the importance and outcomes of local interaction; and the historical legacies that are implicated in constructing places as 'different'. Gappers display a willingness to interact with and gain knowledge about their host communities. Yet as gap years are designed to be distinct from the normal course of things, they also demonstrate the 'difference' of places. This can often result in the reproduction of established ways of representing the Other in order to frame them as meaningful. There is a tension in the narratives between 'globally reflexive' and 'globally reproductive' representations of difference, and I suggest that we might question the development of cosmopolitan attitudes and competencies through undertaking a gap year.